From 'Main Course' to 'Side Dish?' Debates about Removing English as a Core Subject for Chinese Students Receiving Compulsory Education. Issue 1 (2nd January 2023) - Chen, Ningyang; Gu, Chenyang
ABSTRACT: China's impressive growth over the last three decades warrants the need to re-evaluate the position and positioning of English in the country's educational system. For long, English has been taught and learned compulsorily alongside Chinese and maths in primary and secondary schools in the mainland of China. It was not until recent years that the legitimacy of English as a core subject started to be questioned, and calls for alternative solutions began to emerge. For a better understanding of the changing role of English in China's compulsory education and its influence on stakeholders and policymakers, this article investigates the public reaction to a recent controversial proposal to remove English as a core subject from the national curriculum. Drawing from social media comments, autoethnographic reflections, and existing research, the study presents major opinions and attitudes that feature complex sentiments and ambivalences intersected by concerns about equity and balance.